Conflictos socioambientales entre compañías petroleras y las comunidades en el departamento del Casanare (2018)
In the following monograph, a description is given of some of the conflicts (social, environmental and economic), impacts and solutions that have been generated by oil companies such as Ecopetrol and Perenco, and the communities in the department of Casanare. . These factors are studied based on the oil trajectory that the department has had from the last decades to the present. The study exposes several situations that arise in the department of Casanare, due to the development of oil projects and analyzes both companies and communities about what can happen if they do not have good practices when carrying out activities of this type.